Improving Student’s Mathematical Communication Ability through Think Talk Write Learning Model on Geometry Materials - Afrianti, Reny Eka Nur; Qohar, Abd. (Universitas PGRI Madiun, 2020)
This study aimed at investigating the students’ mathematical communication abilities on geometry materials through Think Talk Write (TTW) learning model. The type of research was Classroom Action Research (CAR) with data collection instruments are test of mathematical communication skill, lecturer observation sheets, and student observation sheets. This research was given to 31 first-year students of Malang State University in the academic year 2019/2020. This classroom action research stopped at cycle II. Based on the research results obtained, the percentage of students’ mathematical communication abilities in the first cycle had an average value of 68.097% while that in the second cycle had an average value of 82.000%. The average increase from cycle I to cycle II was 13.903%. Based on the results of the study, it can be concluded that Think Talk Write (TTW) learning model by providing material reinforcement in the form of written summaries as material reinforcement at the end of learning can improve mathematical communication skills of first-level students on geometry materials